A sensitive and specific nanoparticle‐assisted PCR assay for rapid detection of porcine parvovirus. (25th October 2013) - Cui, Y.; Wang, Z.; Ma, X.; Liu, J.; Cui, S.
Abstract A novel nanoparticle‐assisted polymerase chain reaction (nanoPCR) assay to detect porcine parvovirus (PPV) is described here. Primers for this assay were designed based on the conserved region of the nonstructural protein 1 (NS1) gene of PPV, which encodes one of the nonstructural proteins. The sensitivity of the PPV nanoPCR assay was measured by using diluted recombinant plasmids in which the PPV NS1 gene had been inserted. The detection limit was 5·6 × 101 copies μl−1 for the PPV nanoPCR assay vs 5·6 × 103 copies μl−1 for conventional PCR assay. The results showed that the sensitivity of PPV nanoPCR assay was 100 times higher than that of conventional PCR assay. The PPV nanoPCR assay produced 142‐bp product as expected when amplifying PPV DNA, while produced nothing when amplifying the DNA or cDNA of the following viruses: swine encephalomyocarditis virus, classical swine fever virus, porcine pseudorabies virus, porcine reproductive and respiratory syndrome virus, porcine teschovirus and porcine circovirus type II. PPV was detected in 108 of 109 clinical swine samples from Heilongjiang, Jilin and Henan provinces using the nanoPCR assay, and the results were confirmed by sequencing. Significance and Impact of the Study Nanoparticle‐assisted polymerase chain reaction (nanoPCR) assay is an improved PCR. NanoPCR is highly sensitive and specific because the nanofluids formed in the nanobuffer have high thermal conductivity, which reduces the time required to reach the target temperature. It is more sensitive than conventional PCR, and it could detect the cases earlier than conventional PCR. This report describes the first application of the highly efficient nanoPCR technology for the detection of porcine parvovirus (PPV). The PPV nanoPCR assay will be useful for the detection and study of PPV and will also be applicable to improve the detection of other viruses.